Pengaruh Interpersonal Interaction Terhadap Purchase Intention Pada Shopping Live Streaming: Efek Mediasi Swift Guanxi - Nandini, Naomi Marsya; Rahayu, Siti; Trisnawati, â Juliani Dyah (Universitas Jember, 2024)
This study aims to analyze the influence of perceived expertise, perceived similarity, perceived familiarity, perceived likeability, flow, and guidance shopping on swift guanxi and purchase intention. The research was conducted in Indonesia, targeting users of three e-commerce platforms (Shopee, Tokopedia, and Lazada) who have made purchases through shopping live streaming at least one to five times. Respondents were required to be at least 17 years old and have interacted during shopping live streaming sessions. Primary data was collected through questionnaires distributed to a sample of 312 respondents. The study employed a quantitative method using PLS-SEM (Partial Least Square - Structural Equation Modelling) for data analysis. The results indicate that perceived expertise, perceived familiarity, flow, and guidance shopping have a positive and significant impact on swift guanxi, and swift guanxi has a positive and significant impact on purchase intention. However, perceived similarity and perceived likeability do not have a significant influence on swift guanxi. Keywords: Shopping live streaming, Swift guanxi, Purchase intention, Flow, Guidance shopping